Heating rate gradient drives mesostructural dynamics in solid propellant under nonequilibrium conditions - Zhi Jiang; Tianhao Wang; Weichen Sheng; Zechen Li; Chengli Mao; Haolin Luo; Yujian Xia; Wenfeng Shangguan; Chaoyang Zhang; Jiaxing Wang (Proceedings of the National Academy of Sciences, 2025)
Rapid, nonequilibrium heating drives mesoscale structural evolution in heterogeneous composite materials under extreme thermal conditions, critically influencing performance in aerospace propulsion and advanced structural applications. However, existing experimental techniques lack the capability to directly observe heterogeneous structural evolution and intercomponent interactions under controlled conditions that closely mimic realistic nonequilibrium thermal fronts. Consequently, theoretical models, which assume equilibrium conditions or neglect dynamic structural evolution, remain insufficiently validated and cannot accurately predict these critical transformation pathways. Here, we developed a gradiated fast-heating system (>20 °C/s) enabling precise control of heating rate gradients within submillimeter transition regions in a single specimen, seamlessly integrated with sequential synchrotron X-ray tomography and radiography to directly visualize internal structural evolution. This approach allowed capture of diverse structural transformation pathways spanning microsecond-to-millisecond timescales under distinct nonequilibrium thermal conditions, revealing the complete sequence from initial pyrolysis through ignition to final burnout. We found that local heating rates, rather than bulk temperatures, dictate void formation dynamics and fragmentation pathways. In regions with high local heating rates, rapid void nucleation within the binder phase created reticulated porous networks, evolving four times faster than curved interfacial voids observed in adjacent regions experiencing lower heating rates. Furthermore, a cascade of heterogeneous component interactions subsequently fragmented the metallic network into isolated clusters, seeding critical ignition hotspots that governed combustion initiation and propagation mechanisms. These findings indicate that kinetic processes, influenced notably by heating rate, play an important role in mesostructural evolution under nonequilibrium conditions.